Digital transformation and fixed asset turnover in improving the financial performance of manufacturing companies - Lucellia Louise Gerardine Wamaty; Farah Margaretha Leon (Universitas Nusa Cendana, 2026)
Digital transformation has become a strategic imperative for manufacturing firms seeking to enhance financial performance and maintain competitiveness in an increasingly digital business environment. This study examines the effects of digital transformation and fixed asset turnover on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2025 period. A quantitative research design was employed using panel data regression analysis based on 180 firm-year observations selected through purposive sampling. The findings indicate that digital transformation has a positive and significant effect on financial performance, highlighting its role in improving organizational competitiveness and value creation. Fixed asset turnover contributes to cost efficiency but does not significantly enhance profitability. In addition, revenue growth positively influences financial performance, whereas financial leverage negatively affects it. Firm size and firm age are also found to influence cost efficiency. These results underscore the importance of digital transformation and effective asset utilization in strengthening firms' financial outcomes. The study contributes to the growing literature on digitalization and corporate performance by providing empirical evidence from Indonesia's manufacturing sector. However, the analysis is limited to publicly listed manufacturing companies over the 2021–2025 period. Future studies are encouraged to examine other industries, incorporate additional explanatory variables, and employ longer observation periods to provide a more comprehensive understanding of the determinants of financial performance. Keywords: Cost To Revenue Ratio; Digital Transformation; Fixed Asset Turnover; Financial Performance; Manufacturing Companies ; Revenue Growth Rate; Return On Assets